GENDERED POWER AND DISCURSIVE CONTROL: WOMEN'S SUBJECTIVITY IN NJO CHEONG SENG'S ZOEBAIDAH - Sartika Sari; Lia Lisyati; Umar Mukhtar Siregar (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2026)
This research examines the novel Zoebaidah (1940) by Njo Cheong Seng, a prolific Peranakan Chinese author of the early 20th century. This novel was published amidst the dominance of patriarchal discourse in Peranakan Chinese literature, which was mostly written by men. Using feminist narratology, this study analyzes how narrative techniques focused on characterization, focalization, and dialogue construct female subjectivity and negotiate power relations in the text. The research findings reveal that Zoebaidah is constructed ambiguously. She is presented as an intelligent and powerful woman, but is unable to free herself from cultural and customary control. This restrictive cultural construction is what Zoebaidah fights against. She is shown to have critical awareness and the courage to fight against oppressive structures. Zoebaidah's negotiation of patriarchal authority, her rejection of forced marriage, and her willingness to sacrifice personal interests for the sake of shared peace represent a subversive model of femininity. With these findings, this study offers a counter-discourse on women's freedom, identity, and agency, while articulating a critique of patriarchal structures through the construction of resistive and empowered female characters.